Functional-semantic analysis of particles in english (Eurasian Journal of Philology Science and Education, 2018)
The article focuses on one of the topical issues of modern linguistics – particles in modern Englishand their functions. Particle has been out of attention for a long period simply because it was not considered to be a main part of speech. This view-point gradually changed and scientists fairly suggested thatparticle is semantically as powerful and polyfunctional as any other part of speech. During investigation,it became evident that there are two main trends of approaches concerning the status of English particlesas part of speech:1) foreign researchers who never accepted particles as a class of independent parts of speech andadded them to the class of adverbs;2)post-Soviet linguists, who, in their turn, used to allocate particles to the system of secondary partsof speech.In the article both the approaches are considered and it is revealed that they have a common feature– particles implement such meanings as apposition, restriction, and complementation. As a result, it issuggested is that English particles are such units of language that are, firstly, directly related to the communicative goals of the speaker in a specific situation of communication and, consequently, secondly,have an extremely variable semantics, which is refined and completely varies depending on the context.